Genome-wide characterization and expression analysis of LBD transcription factors in Ziziphus jujuba var. spinosa: putative roles in tissue development and abiotic stress adaptation - Li, Meng; Zhang, Qiaoyun; Zhou, Shuhui; Wang, Ruixue; Zhao, Yao; Geng, Jibiao (Frontiers in Plant Science, 2025)
The plant-specific Lateral Organ Boundaries Domain (LBD) transcription factors (TFs) are critical regulators of the expression of genes related to tissue development and stress responses. Sour jujube (Ziziphus jujuba var. spinosa), a stress-tolerant rootstock for jujube cultivation, remains understudied in terms of its LBD gene family. In this study, a genome-wide analysis of the sour jujube genome was performed and 37 ZjLBD genes were identified. These genes were phylogenetically classified into two classes and six subgroups based on evolutionary relationships with Arabidopsis and poplar. These genes were unevenly distributed across 11 chromosomes, with 15 segmental duplication events detected. Upstream TFs of ZjLBDs were predicted and grouped into six interactive networks, revealing that the functions of ZjLBDs may be enriched in stress response, hormone signaling, and tissue development. RNA-seq data demonstrated tissue-specific expression patterns of ZjLBDs, with limited genes highly expressed in fruit. The ZjLBD23 may regulate the development of flowers and white mature fruits, while ZjLBD11, ZjLBD13, ZjLBD22 and ZjLBD28 may be involved in lateral root formation. Analysis of the cis-acting elements, homology relationships and abiotic stress-induced expression levels suggested functional divergence: ZjLBD13, ZjLBD19 and ZjLBD28 may contribute to extreme cold resistance, ZjLBD11, ZjLBD14, ZjLBD33 and ZjLBD35 may be associated with drought tolerance, and ZjLBD9, ZjLBD13 and ZjLBD22 with salt stress adaptation. This study provides critical insights into the biological roles of ZjLBDs and lays a foundation for breeding sour jujube varieties with enhanced stress resilience.